1997
DOI: 10.1074/jbc.272.52.33394
|View full text |Cite
|
Sign up to set email alerts
|

Novel Exonic Elements That Modulate Splicing of the Human Fibronectin EDA Exon

Abstract: Three exons in the fibronectin primary transcript are alternatively spliced in a tissue-and developmental stage-specific manner. One of these exons, EDA, has been shown previously by others to contain two splicing regulatory elements between 155 and 180 nucleotides downstream of the 3-splice site: an exon splicing enhancer and a negative element. By transient expression of a chimeric ␤-globin/fibronectin EDA intron in COS-7 cells, we have identified two additional exonic splicing regulatory elements. RNA gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…Diagram shows a pre-mRNA containing three exons (open boxes) and two introns (lines). Two categories of splicing regulatory elements, splicing enhancers and splicing suppressors (silencers), have been described recently in the exons (grey boxes) or introns (small black boxes) of several viral and mammalian premRNA substrates (94)(95)(96)(97)(98)(99). The heavy-and light-grey boxes in exon 2 are, respectively, exonic splicing enhancers (ESE) and exonic splicing suppressor (ESS) which are often juxtaposed.…”
Section: Figmentioning
confidence: 99%
“…Diagram shows a pre-mRNA containing three exons (open boxes) and two introns (lines). Two categories of splicing regulatory elements, splicing enhancers and splicing suppressors (silencers), have been described recently in the exons (grey boxes) or introns (small black boxes) of several viral and mammalian premRNA substrates (94)(95)(96)(97)(98)(99). The heavy-and light-grey boxes in exon 2 are, respectively, exonic splicing enhancers (ESE) and exonic splicing suppressor (ESS) which are often juxtaposed.…”
Section: Figmentioning
confidence: 99%
“…The splicing inhibitors identified to date appear remarkably diverse (Nemeroff et al 1992;Siebel et al 1992;Amendt et al 1995;Del Gatto and Breathnach 1995;Staffa and Cochrane 1995;Staffa et al 1997;Valcarcel and Gebauer 1997;Grabowski 1998;Zheng et al 1998;Kan and Green 1999;Chou et al 2000;Le Guiner et al 2001;Wagner and Garcia-Blanco 2001). Several proteins with the ability to inhibit splicing have been identified, including two heterogeneous nuclear ribonucleoproteins (hnRNPs), hnRNP A1 and polypyrimidine tract binding protein (PTB or hnRNP I).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these various sites gives rise to at least 35 different mRNAs (1). Although the relative efficiencies of the HIV-1 donor sites seem to depend mainly upon their complementarity to the U1 snRNA 5Ј-terminal sequence (3,4), efficiencies of HIV-1 acceptor sites depend upon the presence of cis-regulatory elements (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Several studies have shown that HIV-1 acceptor sites are suboptimal as follows.…”
mentioning
confidence: 99%
“…Several studies have shown that HIV-1 acceptor sites are suboptimal as follows. (i) Their polypyrimidine tracts are short and interrupted by purines (3,5,9). (ii) Their branch point sequences are not canonical, and in some cases, a residue other than an adenosine is used as the branch site (22,23).…”
mentioning
confidence: 99%